2001
DOI: 10.1063/1.1377626
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystallization of amorphous-Ta40Si14N46 diffusion barrier thin films

Abstract: An optimal quasisuperlattice design to further improve thermal stability of tantalum nitride diffusion barriers Evaluation of single-and multilayered amorphous tantalum nitride thin films as diffusion barriers in copper metallization J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1͑a͒ Ta-N bonding formed regions with less silicon in the TaSiN layer. 9 This can also be explained by the lower formation energy of TaN ͑−120 kJ/ mol͒ compared to TaSi 2 ͑−39 kJ/ mol͒. 14,15 The peak signal of the Si-O bonding at 103.3 eV was not detected in any of the SiN and TaSiN samples.…”
Section: Formation Of Tan Nanocrystals Embedded In Silicon Nitride Bymentioning
confidence: 96%
See 1 more Smart Citation
“…1͑a͒ Ta-N bonding formed regions with less silicon in the TaSiN layer. 9 This can also be explained by the lower formation energy of TaN ͑−120 kJ/ mol͒ compared to TaSi 2 ͑−39 kJ/ mol͒. 14,15 The peak signal of the Si-O bonding at 103.3 eV was not detected in any of the SiN and TaSiN samples.…”
Section: Formation Of Tan Nanocrystals Embedded In Silicon Nitride Bymentioning
confidence: 96%
“…7,8 However, with increases in the silicon concentration in the TaSiN layer and under high annealing temperatures, it is well known that phase separation occurs by spinodal decomposition. 9 Consequently, the TaSiN layer is separated into two stable phases: transition metal nitride and covalent silicon nitride. Bicker et al reported that transition metal nitride was separated as crystalline nanoparticles in an amorphous SiN matrix.…”
Section: Formation Of Tan Nanocrystals Embedded In Silicon Nitride Bymentioning
confidence: 99%